Inspection of a novel penetration enhancer for transungual drug delivery system: Pelargonium hortorum - Singh, Vikram; Chandrul , Kaushal Kishore (Journal of Applied Pharmaceutical Research, 2015)
This study was to search some natural penetration enhancer and formulate them in a transungual drug delivery formulation. This natural penetration enhancer helps to overcome the main problem in front of success of transungual drug delivery system. We selected to formulate fluconazole as a model drug for the nail fungal infection treatment with extracted penetration enhancer (PE). Model drug i.e. fluconazole was formulated with the natural extracted penetration enhancer with different deigned formula. The solvent for PE extraction was methanol and that extracts were air dried. The cadaver human nail plates were used for penetration study, were collected from the same volunteer for negligence in the thickness and chemical composition concentration in the nail plate. The extracted PE (pelargonium hortorum) was selected for formulation on the basis of ethanopharmaceutical history. The human cadaver nail plates were treated with the formulation with and without the extracted PEs. Ex - vivo drug penetration was evaluated by Franz diffusion cells using cadaver human nail plate upto 36 hours. The drug filmability was found to be best with the polymer like HPMC K4M, Ethyl cellulose and hydroxyl propyle cellulose in the ratio of 1:1:1, mixture of propanol and butanol in 7:3 as solvent and 30% w/w DBP as plasticizer. The formula FT25AP4 shows total 35.67% drug penetraion i.e. near about two times of drug penetration across the nail plate when compare to the same formulation but without any penetration enhancer. The “p” value (0.0011) of drug penetration was less than 0.05.